I was trying to solve a problem today when I felt that if the following is proved, we are done:

$(1+a)^y<(1+ay)$ for $0<y<1$ for all non-zero reals a,y.I am not able to make much progress on this one.Can anyone please help me on this?

As always,thank you.

  • $\begingroup$ The inequality cannot be strict. At least not for the restrictions you have placed(or haven't) on a and y. For, if $a=0$ and $y \in (0,1)$ you have equality. Seems like restricting a to non-zero real values might make a better hypothesis. $\endgroup$
    – Arkady
    Jan 29, 2012 at 10:41
  • $\begingroup$ I have edited the question. $\endgroup$
    – Eisen
    Jan 29, 2012 at 10:43
  • 1
    $\begingroup$ If you're familiar with the version of Bernouli's inequality that says $1+rx<(1+x)^r$ when $r>1$, $x>-1$, $x\neq 0$, then this follows from setting $rx=a$, $y=\frac{1}{r}$, and taking the $y$ power of both sides. $\endgroup$ Jan 29, 2012 at 10:52

1 Answer 1


First method: convexity.

The function $v:a\mapsto(1+a)^y$ has second derivative $v''(a)=y(y-1)(1+a)^{y-2}\lt0$ at $a\gt-1$ hence $v$ is concave on $a\geqslant-1$. Since $v'(0)=y$, $t:a\mapsto1+ay$ is the equation of its tangent at $a=0$. The graph of a concave function lies below each of its tangents hence $v(a)\lt t(a)$ at every $a\gt-1$ except $a=0$ where $v(0)=t(0)$ and we are done.

Second method: logarithms.

Let $u(a)=\log(1+ay)-y\log(1+a)$. The assertion to prove is equivalent to $u(a)\gt0$. Note that $u(0)=0$ and $u'(a)=\frac{y}{1+ay}-\frac{y}{1+a}=\frac{ay(1-y)}{(1+ay)(1+a)}$ is positive on $a\gt0$ and negative on $a\lt0$. Thus, the function $u:a\mapsto u(a)$ decreases to $u(0)=0$ on $a\lt0$, then increases from $u(0)=0$ on $a\gt0$. In particular, $u(0)=0$ and $u(a)\gt0$ for every $a\gt-1$, $a\ne0$.

Third method: Taylor formula.

Consider once again the function $v:a\mapsto(1+a)^y$. Then $v(a)=v(0)+av'(0)+\frac12a^2v''(x_a)$ for some $x_a$ between $0$ and $a$, by Taylor formula. Now, $v''(x)=y(y-1)(1+x)^{y-2}\lt0$ for every $x\gt-1$, hence $v''(x_a)\lt0$. Since $v(0)=1$, $v'(0)=y$, this leaves us with the inequality $v(a)\lt v(0)+av'(0)=1+ay$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.